Eptesicus nilssonii - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Eptesicus nilssonii (Keyserling et Blasius, 1839) —Northern Bat Ƒespertilio nilssonii Keyserling and Blasius, 1839 p.315; Type locality- Sweden. Eptesicus nilssonii : Mori, 1928 p.293; Tate, 1947 p.90; Ellerman & Morrison-Scott, 1951 p.155; Won, 1968 p.118; Han, 1994 p.45; Won & Smith, 1999 p.11; Son, 2001 p.111; Yoon, 2004 p.81. E. parvus Kishida, 1932 p.2; Type locality- northern Korea; Tate, 1947 p.91. E. nilssonii parvus : Ellerman & Morrison-Scott, 1951 p.155; Won, 1958 p.457; Won, 1967 p.336; Won, 1968 p.120; Corbet, 1978 p.57 (doubtful); Yoshiyuki, 1989 p.168; Yoon, 1992 p.48; Yoon, 2010 p.65. Range: The distribution of E. nilssonii ranges throughout the Korean Peninsula, but the species remains rare in southern Korea (Han et al. 2011; Fig. 35). The northern bat was first recorded in Lanam, Hamgyeongbuk Province and observed in the area surrounding Seoul and Gyeonggi Province (Won 1967; Son 2001; Kim et al . 2015). Remarks: Only the Subspecies Eptesicus nilssonii parvus Kishida, 1932 was recognized for Korea (Won 1968; Yoon 2010). Although Hanák and Horáćek (1986) regarded this subspecies as an erroneous identification of Pipistrellus savii , Yoshiyuki (1989) classified E . nilssonii from Sakhalin and Hokkaido to E . n . parvus . Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on pages 57-58, DOI:10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198